Studi Beberapa Aspek Reproduksi Rajungan (Portunus pelagicus) di Perairan Mayangan, Kabupaten Subang, Jawa Barat - Hermanto, Dedy Tri; Sulistiono, Sulistiono; Riani, Etty (Biospecies, 2019)
Study on some reproductive aspects of blue swimming crab (Portunus pelagicus) in Mayangan waters, Subang, West Java had been conducted for eleven months (Ferbuary-Desember 2003). The blue swimming crab samples (n=556 individuals, consisted of 251 male and 305 female) were caught by fisherman using crab net and trap sized 25x70 cm. This study covered sex ratio, gonad maturity stage (GMS), gonad somatic index (GSI), fecundity and eggs diameter. During the study (carapace width varied from 63,40-159,70 mm for male and 59,30-163 mm for female), sex ratio (male : female) of the crab was 1 : 1,2. Gonad maturity stage of the crab varied from immature to spent condition. Number of the male mature gonad was found higher during February - April, while female one was in February and June. Carapace width of first mature gonad analyzed using by Speraman-Karber method were 101,5 mm (male) and 122,2 mm (female). Gonad somatic index of male and female ranged 0,57-5,59% and 0,35-5,63%, respectively. The highest value of the gonad somatic index was found in June indicating a peak of spawning season of the crab. Fecundity of the crab ranged from 64.380-1.526.600, while egg carried in the abdomen (of ovigerous female) ranged 80.998-1.343.850. The egg diameter varied from 0,09-0,48 mm, with one mode indicating a total spawner.